Sri Aman peat: Settlement observation and geotechnical properties investigation - Norazzlina, M.Sa‘don; Abdul Razak, Abdul Karim; S.N.L., Taib; Edward, Anak Muol; Ling, Benson Jin Yaw; Angela, Ee (IOP Publishing, 2021)
This paper presents the findings from the field observation and site exploration for construction on peat in Sri Aman, Sarawak, Malaysia. A visit to Balai Bomba and Pejabat Metrologi in Sri Aman has been done in August 2019. From the observation and measurement conducted on the two locations of the constructed area on peat shows the settlement, δ recorded ranges from 100 mm to 150 mm. A field sampling for the determination of geotechnical properties of peat has been done in Balai Bomba Sri Aman. The depth of the peat in the area is about 2.88 m and the results show that the peat has high natural moisture content ranges from 900 % to 1400 %. The organic content (OC) for the site is in the range of 70 %-90 % for a depth of 0.5 m to 2.88 m, and categorized as H3, fibrous peat except for the first 0.5 m is 63 % which fall under H5, hemic peat group according to Von Post classification.